DEGRADATION ABILITY AND IDENTIFICATION OF OIL DEGRADATION BACTERIA BY 16S rRNA SEQUENCING - Shaumi, Nurul; Nursyirwani, Nursyirwani; Feliatra, Feliatra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTPollution in the marine environment caused by industrial activity, marine transportation, offshore mining and oil refineries, one of which comes from petroleum contamination. One of  efforts to prevent and to manage oil pollutionwas by the use of oil degrading bacteria. The objective of this research was to examine degradation ability of marine bacteria isolates and identify the bacterial isolate based on 16S rRNA sequence. The research was conducted from March to May 2018. The oil degradation analysis was conducted at Laboratory of Marine Microbiology,Faculty of Fishery and Marine Science, while the molecularidentification of bacteria was done in Genetics Laboratory, Faculty of Mathematics and Natural Sciences, University of Riau. The results showed that five isolates of oil degradation bacteria, selected(BM 1d, BM 7b, BM 7c, BM 14a and BM 14b) were able to degrade crude oil at different concentrations. The highest degradation at 1% concentration is indicated by BM 14b isolate, at 2% concentration was indicatedby BM 1d isolate and at 3% concentration was indicated BM 14b isolate. From the degradation analysis results, three isolates (BM 1d, BM 14a, BM 14b) have the highest degradation ability to determine the type of oil degrading bacteria. The molecular identification results by the 16S rRNA sequencing and BLAST analysis showed that BM 1d isolate were similar to Bacillus sp. (95%), BM 14a isolate were similar to Bacillus flexus (92%) and BM 14b isolate were similar to Bacillus cereus (98%). Keyword : Oil Degradation Bacteria , Crude Oil, 16S rRNA, Bacillus